Tanshinone IIA inhibits cardiomyocyte pyroptosis through TLR4/NF-κB p65 pathway after acute myocardial infarction - Chai, Ruoning; Ye, Zelin; Xue, Wenjing; Shi, Shuqing; Wei, Yi; Hu, Yuanhui; Wu, Huaqin (Frontiers in Cell and Developmental Biology, 2023)
Background: Tanshinone IIA, derived from Radix Salviae Miltiorrhizae (Salvia miltiorrhiza Bunge), constitutes a significant component of this traditional Chinese medicine. Numerous studies have reported positive outcomes regarding its influence on cardiac function. However, a comprehensive comprehension of the intricate mechanisms responsible for its cardioprotective effects is still lacking. Methods: A rat model of heart failure (HF) induced by acute myocardial infarction (AMI) was established via ligation of the left anterior descending coronary artery. Rats received oral administration of tanshinone IIA (1.5 mg/kg) and captopril (10 mg/kg) for 8 weeks. Cardiac function was assessed through various evaluations. Histological changes in myocardial tissue were observed using staining techniques, including Hematoxylin and Eosin (HE), Masson, and transmission electron microscopy. Tunel staining was used to detect cell apoptosis. Serum levels of NT-pro-BNP, IL-1β, and IL-18 were quantified using enzyme-linked immunosorbent assay (ELISA). Expression levels of TLR4, NF-κB p65, and pyroptosis-related proteins were determined via western blotting (WB). H9C2 cardiomyocytes underwent hypoxia-reoxygenation (H/R) to simulate ischemia-reperfusion (I/R) injury, and cell viability and apoptosis were assessed post treatment with different tanshinone IIA concentrations (0.05 μg/ml, 0.1 μg/ml). ELISA measured IL-1β, IL-18, and LDH expression in the cell supernatant, while WB analysis evaluated TLR4, NF-κB p65, and pyroptosis-related protein levels. NF-κB p65 protein nuclear translocation was observed using laser confocal microscopy. Results: Tanshinone IIA treatment exhibited enhanced cardiac function, mitigated histological cardiac tissue damage, lowered serum levels of NT-pro-BNP, IL-1β, and IL-18, and suppressed myocardial cell apoptosis. Moreover, tanshinone IIA downregulated the expression of TLR4, NF-κB p65, IL-1β, pro-IL-1β, NLRP3, Caspase-1, and GSDMD-N pyroptosis-related proteins in myocardial tissue. Additionally, it bolstered H/R H9C2 cardiomyocyte viability, curbed cardiomyocyte apoptosis, and reduced the levels of TLR4, NF-κB p65, IL-1β, pro-IL-1β, NLRP3, Caspase-1, and GSDMD-N pyroptosis-related proteins in H/R H9C2 cells. Furthermore, it hindered NF-κB p65 protein nuclear translocation. Conclusion: These findings indicate that tanshinone IIA enhances cardiac function and alleviates myocardial injury in HF rats following AMI. Moreover, tanshinone IIA demonstrates potential suppression of cardiomyocyte pyroptosis. These effects likely arise from the inhibition of the TLR4/NF-κB p65 signaling pathway, presenting a promising therapeutic target.